The twin radio galaxy TRG J104454+354055. Issue 1 (17th May 2022) - , Gopal-Krishna; Joshi, Ravi; Patra, Dusmanta; Yang, Xiaolong; Ho, Luis C; Wiita, Paul J; Omar, Amitesh
ABSTRACT: We report observations of a bright dumb-bell system of galaxies ( z = 0.162) with the upgraded Giant Metrewave Radio Telescope ( u GMRT), which show that each member of this gravitationally bound pair of galaxies hosts bipolar radio jets extended on 100 kpc scales. Only two cases of such radio morphology have been reported previously, both being dumb-bell systems, as well. The famous first example, 3C 75, was discovered 4 decades ago, and the second case was discovered 3 decades ago. This implies that such 'Twin-Radio-Galaxies' (TRGs) are an exceedingly rare phenomenon. As in the case of its two senior cousins, the bipolar radio jets of the present TRG (J104454+354055) exhibit strong wiggles and are edge-darkened (Fanaroff–Riley class I). However, there are important differences, too. For instance, the jets in the present TRG do not merge and, moreover, show no signs of distortion due to an external crosswind. This makes the present TRG a much neater laboratory for studying the physics of (sideway) colliding jets of relativistic plasma. This TRG has a Wide-Angle-Tail neighbour hosted by another bright galaxy belonging to the same group, which appears to be moving towards the TRG.